(3GdeQcR GdJQHhj aj (B1017 (3jheGs - (3aQjMI, feQs ((3HjQhJs (3dG fGTQs, 2003)
(3jJfGhd gPG GdcJGH JLQHI GdeDda cQFjS ddeQcR GdJQHhj ddHMhK hGdGfeGA hgh eDSSI YGeI eSJbdI eJejRI aj dHfGf dCfgG ehbY GdJNWjW GdJQHhj dCLjGd GdhWf hdgG GdOhQ GdChd aj QSe ehbY GdJQHjI aj dHfGf Ydi NQjWI GdYGde hHjf GdOhd GdfGejI(B. (3hjMGhd GdeDda Cf jVY GdMbGFb GdJj jedcgG HJUQa GdQCj GdYGe hGdWdGH hGdEOGQjjf hCSGJPI GdLGeYGJ GdPjf dG jfNOYhf HGdCHGWjd YfOeG jJYdb GdCeQ HGdJQHjI aj hWfge(B. (3hjbSe GdcJGH Edi bSejf(B: (3GdChd YHGQI Yf Yed JQHhj hJLQHI EOGQjI aj Mjf Cf GdbSe GdKGfj jJfGhd GdeTGQjY hGdGfLGRGJ GdJQHhjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Administration Scolaire; CERD; CRDP; Educational administration; (3GdGOGQI GdJQHhjIs; (3GdeQcR GdJQHhjs